Assessing the need for cultural expertise in civil proceedings: from court’s discretion to the duty to supplement the judge’s extra-legal knowledge - Valentina Capasso (Revista Ítalo-Española de Derecho Procesal)
In recent years, the topic of expert evidence, usually dealt with having hard sciences in mind, has been enriched with a new profile, as the increasing frequency of multicultural proceedings has prompted the debate about the so-called cultural expertise. Obstacles to the use of this type of knowledge, however, result from a certain distrust in the usefulness of soft sciences for the judge and, more generally, from the strong discretion s/he has in deciding whether to admit expert evidence. Both factors will be critically discussed in the present paper.